Realism in Ethnographic Film - Esther, Bala. (Universiti Malaysia Sarawak (UNIMAS), 2006)
The main aim of this thesis is to explore the notion of realism in ethnographic film. It has been suggested that the idea of realism in ethnographic film is imperative in that it can represents the realities of people's life and culture. But nonetheless, this raises the question of whether it is possible for a filmmaker to represent these realities without being subjective. Furthermore, it is argued that one's subject matter do react differently when confronted by filmmakers' very own tools -the camera. This inevitably can reduce the degree of realism in the film. This research reveals that these problems can be reduced in order to maintain a certain degree of realism in an ethnographic film. Specifically in the case of this research is the application of two interrelated but distinct approaches in film making, namely, Cinema Verite and Direct Cinema. The application of both methods enables a film maker to capture a certain degree of reality at reallocation and of ordinary people. This is affirmed by the final result of this research titled 'Silence Must Be Heard', an ethnographic film of the Pa Tik Penan life style known as Molong, in Bario. This project suggests that ethnographic film still reliable as a means to capture every day life of people.